HUMAN VALUES ORIENTATION, WORK ETHICS AND ETHICAL LEADERSHIP ASSESSMENT OF TEACHING AND NON-TEACHING PERSONNEL - Hazel Anne F. Abarentos (Galaxy International Interdisciplinary Research Journal, 2024)
It is vital for the teacher, as one of the most indispensable staff in the education system, to foster work ethics and to be a role model to his/her students. Since there are societal expectations on teacher, every teacher is directed to do what is right. This study determined the human values and work ethics of the teaching and non-teaching personnel of Trece Martires City National High School – Conchu Annex. The study utilized a standardized questionnaire to 19 personnel. The mean responses were high on the human values orientation and very high on the work ethics and ethical leadership. The study recommends that the school personnel should make the improvement on human values orientation by doing seminars, retreat and open forum. A similar study should be conducted every year in order to assess the human values, work ethics and ethical leadership of school personnel annually.